Updates on the Systemic Treatment of Advanced Non-melanoma Skin Cancer - Tanese, Keiji; Nakamura, Yoshio; Hirai, Ikuko; Funakoshi, Takeru (Frontiers in Medicine, 2019)
Non-melanoma skin cancers (NMSCs), which represent a diverse group of cutaneous malignancies, are the most common forms of human neoplasia. The incidence of these diseases is increasing due to a number of factors, including that of increasing human lifespans. The majority of NMSCs are basal cell carcinomas (BCC) and cutaneous squamous cell carcinomas (cSCC), with the remainder being various rare skin cancers, including extramammary Paget’s disease (EMPD), Merkel cell carcinoma (MCC), and several skin adnexal carcinomas. Of these, MCC usually shows aggressive behavior with a high mortality rate. On the other hand, BCC, cSCC, EMPD, and skin adnexal tumors usually show an indolent clinical course and metastasize only rarely. Nevertheless, the metastatic forms of these tumors commonly lead to poor patient outcome. A definitive management strategy for the treatment of advanced NMSC has not been established, mainly due to their rarity and lack of reliable information based on well-controlled randomized trials. Chemotherapeutic regimens for treatment of these diseases have been based mainly on the observations of isolated, small case series or clinical trials with limited numbers of patients. However, accumulating evidence regarding their pathobiological backgrounds as well as recent advances in molecular biotechnology have facilitated the development of novel drugs for treatment of these diseases. Over the past decade, the U.S. Food and Drug Administration has approved several molecular targeting therapies, including Hedgehog inhibitors for BCC, monoclonal antibodies targeting anti-programmed death ligand-1 and anti- programmed cell death 1 (PD-1) for MCC, and anti-PD-1 for cSCC. Here, we review their clinical utility and discuss updated systemic treatment strategies for advanced NMSC.